Optimized Flexural Strength of Aluminium Honeycomb Sandwiches Using Fuzzy Logic Method for Load Bearing Application - Muhammad Yusuf R. Siahaan, Rakhmad Arief Siregar, Faisal Amri Tanjung (International Journal of Intelligent Systems and Applications in Engineering, 2023)
This paper discussed experimental results of flexural behaviour of aluminium honeycomb sandwich panels. The flexural behaviour of the panels is studied using fuzzy logic method and focused on permanent after-impact deflections. The response of aluminium honeycomb sandwich panels to three-point bending impact load was examined with three angles of impact. All specimens were subjected to impact angles of 90°, 60° and 45° at constant impact velocity. Three different cell sizes were used for this study in order to observe permanent after-impact maximum deflections. The results showed that the parameter of cell core sized in a good agreement with deflection increase factor, implying the potential in load-bearing application.